The climates of the world’s wine regions - German Puga; Kym Anderson (IVES Technical Reviews)
The aim of this article is to describe the climates of the world’s wine regions and discuss implications of climate change for those regions. In doing so, we summarise a recent scientific journal article: Puga et al. (2022). We also incorporate insights from other work – part of which is first published here.